New combinations and immunotherapies for melanoma: latest evidence and clinical utility - Menzies, Alexander M. (SAGE Publications, 2013)
Until recently there was no effective systemic therapy for metastatic melanoma. Increased understanding of tumor biology and immune regulation has led to the development of drugs targeting the mitogen-activated protein kinase (MAPK) pathway (BRAF inhibitors and MEK inhibitors) and T-cell regulation (CTLA4 antibodies). These drugs are the new standard of care, however barriers to better patient outcomes include limited responses and significant toxicities (CTLA4 antibodies) and lack of durability in the majority of cases (BRAF and MEK inhibitors). This review discusses the next stages of development of treatments in melanoma, including immune checkpoint blocking drugs targeting the PD-1/PD-L1 axis, and the use of BRAF and MEK inhibitors in combination. Both approaches lead to a higher proportion of durable responses coupled with less toxicity. In an effort to improve outcomes even further, clinical trials of combinations of MAPK inhibitors, immunotherapies and other signal pathway inhibitors are underway. Adjuvant studies of many of these drugs have commenced, with the hope of also improving outcomes in patients with early-stage melanoma.